(untitled) (Педагогіка вищої та середньої школи, 2009)
The technics of water colour painting possesses unique specificity Variability of this technics is done by almost impossible its copying, and extreme fragility, propensity in management and mob’ deliver to Students many efforts, first of all in a choice of methods and techniques And. though till now there are disputes concerning waler colour definition at schedules nr painting, clearly, that It hat specific propertics of both art forms.